Brief Interventions Implementation on Alcohol from the European Health Systems Perspective - Colom, Joan; Scafato, Emanuele; Segura, Lidia; Gandin, Claudia; Struzzo, Pierluigi (Frontiers in Psychiatry, 2014)
Alcohol related health problems are important public health issues and alcohol remains one of the leading risk factors of chronic health conditions. In addition, only a small proportion of those who need treatment access it, with figures ranging from 1 in 25 to 1 in 7. In this context, Screening and Brief Interventions (SBI) have proven to be effective in reducing alcohol consumption and alcohol related problems in primary health care (PHC) and are very cost effective, or even cost-saving, in PHC. Even if the widespread implementation of SBI has been prioritized and encouraged by the WHO, in the global alcohol strategy, the evidence on long term and population level effects is still weak. This review study will summarize the SBI programs implemented by six European countries with different socio-economic contexts. Similar components at health professional level but differences at organizational level, especially on the measures to support clinical practice, incentives and monitoring systems developed were adopted. In Italy cost-effectiveness analyses and Internet trials shed new light on limits and facilitators of renewed, evidence-based approaches to better deal with brief intervention in PHC. The majority of the efforts were aimed at overcoming individual barriers and promoting health professionals’ involvement. The population screened have been in general too low to be able to detect any population level effect, with a negative impact on the acceptability of the program to all stakeholders. This paper will present a different point of view based on a strategic broadening of the implemented actions to real inter-sectoriality and a wider holistic approach. Effective alcohol policies should strive for quality provision of Health Services (HS) and the empowerment of the individuals in a Health System (HSys) approach.